The Effect of Special Allocation Funds and Capital Expenditures on Economic Growth in Regency/City Governments in North Sumatra Province - Deddy Dharma Putra (ProBisnis : Jurnal Manajemen, 2020)
This study aims to identify and examine whether the special allocation funds and capital expenditures effect on economic growth in regencies / cities in North Sumatra Province in 2012-2014. The data used in this research is secondary data obtained from the Ministry of Finance of the Republic of Indonesia, Directorate General of Fiscal Balance www.djpk.depkeu.go.id through the site, and the Central Bureau of Statistics through www.bps. go.id/sumut site. Total population of this study a total of 33 District / City by using purposive sampling obtained 12 regencies / cities as samples. Observation data for 3 years (2012-2014) so ​​that the analysis of observations into 36 data. The analytical method used to test the hypothesis is multiple regression analysis. The results showed that the variable Simultaneously special allocation of funds and capital expenditure had a significant effect on economic growth at the Regency / City in the province of North Sumatra in 2012-2014. Partially variable earmarked grants and capital expenditures positive and significant impact on economic growth at the Regency / City in the province of North Sumatra in 2012-2014.